Estimasi Biaya Perangkat Lunak Menggunakan Metode Function Point Analysis (Studi Kasus: Sistem BKD Universitas XYZ) - Puspitasari, Reinindhi; Nugraini, Dian; Dewi, Renny Sari (JURIKOM (Jurnal Riset Komputer), 2019)
Software effort estimation was considered importantly in planning stage of information technology and communication projects as a determination of resource allocation. The level of accuracy in estimating the cost that must be done in order to minimize failure. On the other hand, there have been many studies that have discussed and tested the business estimation method, one of which is Function Points (FP). The FP method is influenced by 5 main parameters and 14 items relative complexity factors. So it can be concluded that if, a tertiary education institution, wants to develop an BKD (Lecturer Performance Load) application to support its business processes, the required cost is IDR 42,181,198 or equivalent to an effort of 3,273.11 man / hour.